Difference between revisions of "009A Sample Final 3, Problem 7"
Jump to navigation
Jump to search
(Created page with "<span class="exam">Compute <span class="exam">(a) <math style="vertical-align: -18px">\lim_{x\rightarrow 0} \frac{x}{3-\sqrt{9-x}}</math> <span class="exam">(b) ...") |
|||
Line 10: | Line 10: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |'''L'Hôpital's Rule''' | + | |'''L'Hôpital's Rule, Part 1''' |
|- | |- | ||
− | | | + | | |
+ | Let <math style="vertical-align: -12px">\lim_{x\rightarrow c}f(x)=0</math> and <math style="vertical-align: -12px">\lim_{x\rightarrow c}g(x)=0,</math> where <math style="vertical-align: -5px">f</math> and <math style="vertical-align: -5px">g</math> are differentiable functions | ||
|- | |- | ||
− | | | + | | on an open interval <math style="vertical-align: 0px">I</math> containing <math style="vertical-align: -5px">c,</math> and <math style="vertical-align: -5px">g'(x)\ne 0</math> on <math style="vertical-align: 0px">I</math> except possibly at <math style="vertical-align: 0px">c.</math> |
− | | ||
|- | |- | ||
− | | | + | | Then, <math style="vertical-align: -18px">\lim_{x\rightarrow c} \frac{f(x)}{g(x)}=\lim_{x\rightarrow c} \frac{f'(x)}{g'(x)}.</math> |
− | | ||
|} | |} | ||
Line 44: | Line 43: | ||
|- | |- | ||
| <math>\begin{array}{rcl} | | <math>\begin{array}{rcl} | ||
− | \displaystyle{\lim_{x\rightarrow 0} \frac{x}{3-\sqrt{9-x}}} & = & \displaystyle{\lim_{x\rightarrow 0} \frac{x}{3-\sqrt{9-x}}\frac{(3+\sqrt{9 | + | \displaystyle{\lim_{x\rightarrow 0} \frac{x}{3-\sqrt{9-x}}} & = & \displaystyle{\lim_{x\rightarrow 0} \frac{x}{3-\sqrt{9-x}}\frac{(3+\sqrt{9-x})}{(3+\sqrt{9-x})}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{\lim_{x\rightarrow 0} \frac{x(3+\sqrt{9 | + | & = & \displaystyle{\lim_{x\rightarrow 0} \frac{x(3+\sqrt{9-x})}{9-(9-x)}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{\lim_{x\rightarrow 0} \frac{x(3+\sqrt{9 | + | & = & \displaystyle{\lim_{x\rightarrow 0} \frac{x(3+\sqrt{9-x})}{x}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{\lim_{x\rightarrow 0} \frac{3+\sqrt{9 | + | & = & \displaystyle{\lim_{x\rightarrow 0} \frac{3+\sqrt{9-x}}{1}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{ \frac{3+\sqrt{9}}{ | + | & = & \displaystyle{ \frac{3+\sqrt{9}}{1}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{ | + | & = & \displaystyle{\frac{6}{1}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{ | + | & = & \displaystyle{6.} |
\end{array}</math> | \end{array}</math> | ||
|- | |- | ||
Line 121: | Line 120: | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | '''(a)''' <math> | + | | '''(a)''' <math>6</math> |
|- | |- | ||
| '''(b)''' <math>1</math> | | '''(b)''' <math>1</math> |
Latest revision as of 17:14, 20 May 2017
Compute
(a)
(b)
(c)
Foundations: |
---|
L'Hôpital's Rule, Part 1 |
Let and where and are differentiable functions |
on an open interval containing and on except possibly at |
Then, |
Solution:
(a)
Step 1: |
---|
We begin by noticing that we plug in into |
we get |
Step 2: |
---|
Now, we multiply the numerator and denominator by the conjugate of the denominator. |
Hence, we have |
(b)
Step 1: |
---|
We proceed using L'Hôpital's Rule. So, we have |
|
Step 2: |
---|
Now, we plug in to get |
(c)
Step 1: |
---|
We begin by factoring the numerator and denominator. We have |
|
So, we can cancel in the numerator and denominator. Thus, we have |
|
Step 2: |
---|
Now, we can just plug in to get |
Final Answer: |
---|
(a) |
(b) |
(c) |